Mathematical study of the small oscillations of a finite cylindrical column liquid-gas under zero gravity - Essaouini, Hilal; Capodanno, Pierre (Global Journal of Mathematical Analysis, 2019)
This paper deals with the mathematical study of the small motions of a system formed by a cylindrical liquid column bounded by two parallel circular rings and an internal cylindrical column constituted by a barotropic gas under zero gravity. From the equations of motion, the authors deduce a variational equation. Then, the study of the small oscillations depends on the coerciveness of a hermitian form that appears in this equation. It is proved that this last problem is reduced to an auxiliary eigenvalues problem. The discussion shows that, under a simple geometric condition, the problem is a classical vibration problem.Â Â